THE IMPACT OF DIFFERENT KINDS OF MINERAL NUTRITION ON GROWTH AND DEVELOPMENT OF SPRING BARLEY IN THE STEPPE ZONE OF UKRAINE - Masliiov, S. V.; Korzhova, N. A.; Yarchuk, I. I.; Luklyanchuk, V. F. (Scientific Progress & Innovations, 2019)
Climate change has been observed in recent years, which leads to changing the approaches to conven-tional spring grain cultivation technologies. An important aspect of this issue is to obtain stable yields re-gardless of weather conditions of the growing period. A scientifically substantiated fertilization system re-duces the impact of negative factors on plants, ensuring high productivity and quality management of spring barley grain. The main objective of the proposed fertilization system is to disclose the crop biological poten-tial. This can be achieved by establishing balanced fertilizer rates, corresponding terms of their application, which enables to optimize the processes of nutrient absorption and uptake by plants. Therefore, the purpose of this work was to investigate the influence of different mineral nutrition types on the growth and develop-ment of spring barley plants in the Steppe zone of Ukraine. The task was to determine the spectrum of miner-al preparations’ effect: on the length of the aboveground and underground parts, the area of leaf surface and the productivity of spring barley plants. The main research methods were field and laboratory. The re-search was carried out on the experimental plots of the Department of Biology and Agronomy, in the De-partment of agrarian scientific-technical training of Luhansk Taras Shevchenko National University (Luhansk oblast, Starobilsk district). The results of the studies show that the mineral nutrition background made by applying fertilizers influenced the growth and development of spring barley plants during the grow-ing period. Fertilizing resulted in changing the linear parameters of spring barley, such as the height of the aboveground part and the length of the underground part. For intensifying the aerial part of spring barley plants, it is advisable to use ActiBION preparation in combination with ammonium nitrate, as the parame-ters increased from 2 to 16 cm compared with the control. Using the preparations in any amount has led to increase in the root system, and thus to an increase in the plants’ absorption capacity, which leads to in-creased immunity of each object under the study. Thus, the largest length of the root system was observed in the variant with the ActiBION combined using with ammonium nitrate and reached 3 cm increase at the stage of milky ripeness in comparison with the control. The largest lamina area was ensured by the com-bined applying ActiBION preparations with ammonium nitrate. The area increased by 18.2 cm2 as compared with the control. During 2017−2019, there was yield increase of spring barley under the influence of differ-ent types of mineral nutrition. The highest yields were obtained in 2019 in the variant of combining ActiBI-ON and ammonium nitrate, slightly lower yields were in 2017−2018, due to the sharp weather changes in the spring. But they increased within 5−16 hundredweight/ha in comparison with the control, which showed the optimization of absorption and assimilation processes of the nutrients by spring barley plants.